Konstitusin blong Ripablik blong Vanuatu (Niu Hebredis), 1980 ([publisher not identified], 1980)
"On 7/30/80 Vanuatu, the former Anglo-French condominium of the New Hebrides, became independent." Cf. OCLC ARN 00638358, New Hebrides.